The Role of Psychoeducation in Raising Awareness About Gifted Children Towards Teachers - Medellu, Gita Irianda Rizkyani; Issom, Fitri Lestari; Sy, Vinna Ramadhany (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2022)
Certain phenomena have been found within our target for Community Service activity of the Faculty of Psychology Education, the State University of Jakarta, which is taking place at SMPN 139, Jakarta. The issue that arose from the target school is despite being an inclusive school, the understanding among the teachers still lacks regarding particular special needs of students. The stigma said that Gifted children were considered an advantage; they thought Gifted children didn't need special treatment and managing adaptable programs to facilitate Gifted children. In fact, special need children even Gifted one still need to optimize their capacities with the proper program that could be managed by the school. In an effort to increase this awareness, teachers will be involved this community service, which includes several activities. Our program mainly focused on Psychoeducation in the form of webinars through material presentations, video, discussion. The result of the community Service program at SMPN 139 Jakarta showed the significant differences between the results before giving psychoeducation program, and after the program, it means there was an effect of providing Psychoeducation about gifted students to increase the awareness of teachers at SMPN 139 East Jakarta.